Avaliação das propriedades físicas, químicas e térmicas dos pellets de madeira - Camargo, Bruno Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Through the tremendous growth of global energy, the increase in the search for new sources of energy becomes continuous and constant. Due to the current shortage of non-renewable and highly polluting, such as oil and coal, forest biomass and its derivatives, the use of wood pellets emerges as a form of alternative energy, as they have great potential, besides supplying energy needs still provides less environmental impact . The wood pellets are usually produced from lignocellulosic materials, agribusiness and forestry (which may be coming in the form of wast), the materials are refined and dried and then be compressed and compressed at high pressure. The objective of this study was to compare the main chemical characteristics (fixed carbon, volatile, ash, extractives, lignin and holocellulose), physical characteristics (length, diameter, bulk density, moisture content and mechanical durability), thermal characteristics (calorific value), pH and conductivity and thermal emissions gases ( CO, CO2, SOx and NOx). We analyzed three types of pellets (one Eucalyptus ssp., One pine ssp. Pine and ssp. Containing 15% charcoal), the analyzes were performed according to standard norms. For gas analysis was used electrochemical gas analyzer to check the amount of gases in the combustion of pellets. The analyzes indicated that the pellets had higher P1 value PCS0% to 20.52 MJ / kg. The pellets P1 compared with the other feature most energetic power. With respect to the moisture content, the results showed that all the pellets reached this quality parameter. As for the mechanical durability all pellets are above the minimum required by the standard. The bulk density of biofuels also achieved this quality parameter, since all showed values exceeding 600 kg / m³ which is the minimum required by the rules (German, Austrian, Swedish and America) . Regarding the gaseous emissions of CO, all pellets had values above the...

Atráves do grande crescimento da matriz energética mundial, o aumento pela busca de novas fontes de energia torna-se contínuo e constante. Devido a escassez de atuais fontes não renovavéis e altamente poluentes, como o petróleo e o carvão mineral, a biomassa florestal e seus produtos derivados como os pellets e briquetes de madeira por exemplo, surgem como uma forma de energia alternativa, já que possuem grande potencial, além de suprir as necessidades de energia ainda proporciona menor impacto ambiental. Os pellets de madeira geralmente são produzidos a partir de materiais lignocelulósicos, como por exemplo, resíduos do setor madeireiro, agroindustrial e florestal. O objetivo deste trabalho foi comparar diferentes tipos de pellets quanto as propriedades químicas (pH, condutividade iônica, poder calorífico, carbono fixo, materiais voláteis e cinzas), propriedades físicas (comprimento, diâmetro, densidade a granel, teor de umidade e durabilidade mecânica) e da combustão (emissões de gases CO, CO2, SOx e NOx) entre si e segundo as Padrões Internacionais de Qualidade para pellets. Foram analisados três tipos de pellets (de Pinus ssp. com 15% de teor de finos de carvão vegetal (P1), maravalhas de Pinus ssp.(P2) e maravalhas de Eucalyptus ssp.(P3)). As análises de caracterização foram realizadas conforme as normas padrões. Para análise dos gases foi utilizado um analisador eletroquímico de gases, para verificar a quantidade de gases presentes na combustão dos pellets. As análises realizadas indicaram que os pellets P1 tiveram maior valor de PCS0% com 20,52MJ/kg. Os pellets P1 se comparados com os demais apresentam maior poder energético. Com relação ao teor de umidade, os resultados mostraram que todos os pellets atingiram esse parâmetro de qualidade. Quanto a durabilidade mecânica todos os pellets estão acima dos valores mínimos exigidos pela norma. A densidade a granel dos biocombustíveis também atingiram...
Keywords: Pellets de madeira; Biomassa vegetal; Energia - Fontes alternativas; Residuos de madeira como combustivel; Wood pellets